Effect of the STAD Model Assisted by Wordwall on Junior High School Students’ Biotechnology Learning Outcomes - Feby Alvyolyn Ujung; Idramsa Idramsa (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
The low learning outcomes of students in biotechnology indicate the need for innovative, collaborative, and technology-integrated learning strategies that are aligned with the characteristics of learners in the digital era. This study aimed to analyze the effect of the Student Teams Achievement Division (STAD) cooperative learning model, assisted by Wordwall media, on students’ learning outcomes in biotechnology at SMP Negeri 23 Medan. This study employed a quasi-experimental design with a nonequivalent control group. The sample consisted of 62 students, including 31 students in the experimental class and 31 students in the control class, selected through purposive sampling. The research instrument was a 20-item multiple-choice cognitive achievement test that had been validated and shown to be reliable. Data were analyzed using descriptive and inferential statistics, including the Shapiro-Wilk normality test, Levene’s homogeneity test, and the Independent Samples t-test at a 5% significance level. The results showed that the experimental class's mean posttest score (75.48) was higher than the control class's (59.84). Hypothesis testing revealed a Sig. (2-tailed) value of < 0.001, indicating that the STAD learning model assisted by Wordwall had a significant effect on students’ learning outcomes. These findings demonstrate that integrating cooperative learning with interactive digital media can increase student engagement, strengthen conceptual understanding, and serve as an innovative instructional strategy for teaching conceptual and abstract science topics.